Supporting and Inhibiting Factors of Priority Service Risk Management Implementation in Islamic Banks: Empirical Evidence from OJK Regulation 57/2016 - Firmansyah, Dinata; Bin Mohammad, Che Adenan (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study examines the supporting and inhibiting factors in the implementation of OJK Regulation No. 57/POJK.03/2016 on risk management for priority customer services at Bank Muamalat Cirebon Branch.Design/Methodology: Using a qualitative approach with a post-positivist paradigm, data were collected through interviews, observations, and documentation. The analysis applies Mazmanian and Sabatier’s implementation framework, supported by triangulation techniques to ensure validity.Findings: The results show that leadership commitment, organizational capacity, and clear policy guidance act as supporting factors, while the absence of Relationship Managers and Priority Centers, slow responsiveness, limited staff training, and unclear performance indicators hinder effective implementation. To address these challenges, the bank has planned initiatives such as establishing a Priority Center, enhancing staff competencies through specialized training, improving responsiveness, and strengthening monitoring and evaluation processes.Practical Implications:The study offers practical insights for Islamic banks on managing risks and enhancing priority customer services in accordance with regulatory requirements. It also offers recommendations for policymakers to strengthen supervisory frameworks.Originality/Value: Unlike previous studies, this research focuses on the intersection of regulatory compliance and service quality in Islamic banking, contributing original insights into the challenges and strategies of implementing risk management for priority customers.